Risk factors for pre-eclampsia among women at antenatal booking in Kano, Northern Nigeria - Ibrahim A. Yakasai; Imran O. Morhason-Bello (PAGEPress Publications, 2013)
Pre-eclampsia (PE) is an important cause of maternal mortality. There have been several studies on risk factors assessment with conflicting reports across the globe on this disease; however, rigorous recent evaluation of these factors is uncommon in this region. The aim of the present study was to determine the risks factors in the early-onset PE in Aminu Kano Teaching Hospital (AKTH), Kano (Northern Nigeria). We conducted a case-control study in Nigeria between April 2009 and January 2010 to identify the risk factors associated with the early-onset PE in women attending antenatal clinic in AKTH. Information on socio-cultural characteristics, medical history, previous obstetrics history, level of stress at home, and type of family were obtained and recorded in a proforma designed for the study. Multiple logistic regression analysis was used to determine the risk factors for PE at 95% confidence level. Pregnant women with early-onset PE (150 in each case and control group). Risk factors associated with increased risk of early-onset PE were: history of pre-eclampsia/eclampsia (PE/E) in a previous pregnancy [adjusted odds ratio (AOR) 2.09]; exposure to passive smoking (AOR 1.34); inadequate antenatal supervision (AOR 15.21); family history of hypertension in one or more 1st-degree relative (AOR 8.92); living in a joint family (AOR 6.93); overweight (120% to 150% of pre-pregnancy ideal body weight, AOR 4.65). Risk factors among women in Northern Nigeria are similar to those reported from other studies. Good antenatal cares, early detection, reduction of stressful conditions at home are the most important preventive measures of early-onset severe PE among these women.